Purchasing power intention of counterfeit sports goods among customs officers of Wilayah Persekutuan Kuala Lumpur (WPKL) / Nur ‘Atiqah Osman - Osman, Nur ‘Atiqah (Faculty of Business and Management, 2019)
The purpose of this study is to examine the determinants of purchasing power intention on counterfeit, but focusing more on sports goods based on the Theory of Planned Behavior among the Customs officers that working at Wilayah Persekutuan Kuala Lumpur (WPKL). Survey data was collected among 148 respondents from Customs officers of (WPKL). Non-probability technique and convenience technique has been used as a sampling technique. The data collected then were key in by using SPSS (Statistical Package for Social Science) version 20.0 to be analyzed. Based on the data obtained, two independent variables which are attitude and subjective norms have a positive relationship and significantly influence the purchasing power intention of counterfeit sports goods, whereas perceived behavioral control and brand consciousness has no significant relationship associated with purchasing power intention of counterfeit sports goods.